Total cell-free DNA, carcinoembryonic antigen, and C-reactive protein for assessment of prognosis in patients with metastatic colorectal cancer. Issue 11 (November 2018) - Spindler, Karen-Lise Garm; Demuth, Christina; Sorensen, Boe Sandahl; Johansen, Julia S; Nielsen, Dorte; Pallisgaard, Niels; Hoegdall, Estrid; Pfeiffer, Per; Vittrup Jensen, Benny
In late-stage metastatic colorectal cancer, difficult treatment decisions should incorporate a thorough evaluation of the patient's general condition and subject for shared decision making. Assessment of the individual patients' prognosis is valuable in this setting. The aim was to analyze the prognostic value of plasma levels of total cell-free DNA, carcinoembryonic antigen and C-reactive protein in 97 heavily pretreated patients with metastatic colorectal cancer. Patients received irinotecan, cetuximab, and everolimus in a phase-2 clinical trial (clinicaltrials.gov NCT01387880). Plasma samples were used for DNA purification and quantification of total cell-free DNA by droplet digital polymerase chain reaction. Serum carcinoembryonic antigen and C-reactive protein were analyzed by routine methods. Clinical endpoints were overall survival and progression-free survival. A total of 82 patients had blood samples available for quantification of total cell-free DNA. Patients with pre-treatment cell-free DNA levels higher than the median total cell-free DNA (9800 alleles per milliliter plasma) had a significantly shorter overall survival of 4.3 months (95% confidence interval: 3.6–5.8) compared to patients with cell-free DNA levels below the median with an overall survival of 11.3 months (95% confidence interval: 8.0–14.8, p < 0.0001). When using the upper normal limit from a previously analyzed normal control group, the median overall survival was 11.3 (95% confidence interval: 7.3–14.8) and 4.3 (95% confidence interval: 3.7–6.1) months, respectively (p < 0.0001). Serum carcinoembryonic antigen and C-reactive protein had similar prognostic value with short overall survival and progression-free survival in patients with elevated levels compared to those within normal range. A high-risk profile of elevated cell-free DNA, carcinoembryonic antigen, and C-reactive protein was described, but in combined Cox regression multivariate analysis, only total cell-free DNA preserved a strong prognostic value. In conclusion, total cell-free DNA in plasma, carcinoembryonic antigen, and C-reactive protein could all contribute to assessment of patients' prognosis and potentially aid in clinical decision making in patients with metastatic colorectal cancer.